Value of cardiac MRI for evaluation of chronic Chagas disease cardiomyopathy. Issue 6 (June 2016) - Lee-Felker, S.A.; Thomas, M.; Felker, E.R.; Traina, M.; Salih, M.; Hernandez, S.; Bradfield, J.; Lee, M.; Meymandi, S.
Abstract : Aim: To determine whether cardiac magnetic resonance imaging (cMRI) is more sensitive than electrocardiogram (ECG) and echocardiogram (ECHO) for detecting myocardial involvement in a Latin American migrant population with untreated Chagas disease (CD) in the United States. Materials and methods: All untreated CD patients with ECG and ECHO examinations who underwent cMRI at Olive View-UCLA Medical Center from September 2010 to December 2013 ( n =81) were analysed in three groups: Group 1, normal ECG and ECHO examinations ( n =50); Group 2, abnormal ECG and normal ECHO examinations ( n =10); and Group 3, abnormal ECHO examination ( n =21). Frequencies of ECG, ECHO, and cMRI findings were compared across groups. Results: Seventy percent (57/81) of the study population was female, with a mean age of 47 years (range, 17–77 years). Twenty-six percent (21/81) had delayed myocardial enhancement (DME), which was most commonly inferolateral in location (27%, 32/117 segments) and transmural in pattern (56%, 65/117 segments). Eight percent (4/50), 30% (3/10), and 67% (14/21) of Groups 1–3, respectively, had DME. Of these individuals with DME, 50% (2/4), 67% (2/3), and 100% (14/14) of Groups 1–3, respectively, also had wall motion abnormality (WMA) on cMRI. In addition to the highest percentages of DME and WMA, Group 3 also had significantly higher mean myocardial mass ( p< 0.01), mean left ventricular end-diastolic ( p< 0.01) and end-systolic volumes ( p< 0.0005), and significantly lower mean left ventricular ejection fraction ( p< 0.001). Conclusion: cMRI may detect myocardial involvement in untreated CD that is otherwise unrecognised on ECG and ECHO. Highlights: Chagas disease (CD) is becoming more common outside Latin America, especially in the United States. CD is often asymptomatic, with undetected myocardial involvement. Cardiac magnetic resonance imaging may identify myocardial involvement prior to electrocardiogram and echocardiogram changes. Early detection helps identify those at high risk for morbidity and mortality.